2011
DOI: 10.1186/1475-2891-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Food for thought: an exploratory study of how physicians experience poor workplace nutrition

Abstract: BackgroundNutrition is often a casualty of the busy work day for physicians. We aimed to explore physicians' views of their nutrition in the workplace including their perceptions of the impact of inadequate nutrition upon their personal wellness and their professional performance.MethodsThis is a qualitative study of a sample of 20 physicians practicing in a large urban teaching hospital. Semi-structured open ended interviews were conducted to explore physicians' views of workplace nutrition. The same physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 18 publications
3
46
0
1
Order By: Relevance
“…In terms of research studies, there are only a few studies that have looked at physician nutrition. These studies all suggest that physicians and residents do not eat or drink adequately during working hours 3 5 6 38 39. In two Canadian studies, physicians and on-call residents in an urban teaching hospital reported that inadequate food intake and dehydration during their working hours had negative impacts on their work performance and sense of well-being 5 6.…”
Section: Current Status Of Physician Nutrition and Barriers To Healthmentioning
confidence: 99%
“…In terms of research studies, there are only a few studies that have looked at physician nutrition. These studies all suggest that physicians and residents do not eat or drink adequately during working hours 3 5 6 38 39. In two Canadian studies, physicians and on-call residents in an urban teaching hospital reported that inadequate food intake and dehydration during their working hours had negative impacts on their work performance and sense of well-being 5 6.…”
Section: Current Status Of Physician Nutrition and Barriers To Healthmentioning
confidence: 99%
“…In a survey among 763 American physicians, their excessive number of work hours was associated with lack of exercise, not eating breakfast, and sleeping fewer than six hours per night. Physicians report that inadequate personal workplace nutrition has a significant negative impact on their personal wellness and professional performance (Lemaire et al, 2011). The workplace, as we showed in a previous dietary intervention trial, could be a successful platform for lifestyle intervention (Shai et al, 2008).…”
Section: Mean (Sd) Mean (Sd)mentioning
confidence: 63%
“…We examined the following comorbidities: diabetes (ICD-9-CM code 250), hyperlipidemia (ICD-9-CM code 272), hypertension (ICD-9-CM codes 401 to 405), peptic ulcer disease (ICD-9-CM codes 531−534.9), autoimmune disease (ICD-9-CM codes 710.0, 710. 6), and end-stage renal disease (ESRD) (ICD-9-CM code 585). The baseline comorbidities that may be associated with cancer were identified before the end dates (the date of cancer diagnosis, date the patient was lost to follow-up, date of death, date of withdrawal from insurance or last day of 2010) subjects in both cohorts.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Physicians who are unwell mentally or physically are less able to coordinate their practice with the broader health care system and thus are more prone to providing suboptimal patient care. Numerous studies have investigated the mental health, on-call hours, work loading, workplace nutrition, or health behaviors of physicians and the associated impact on medical errors 5,6) . The research on physical health of physicians has been limited, and has often focused on mortality analysis 7,8) .…”
mentioning
confidence: 99%